2005
DOI: 10.1111/j.1537-2995.2005.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety of platelets photochemically treated with amotosalen HCl and ultraviolet A light for pathogen inactivation: the SPRINT trial

Abstract: The overall safety profile of PCT PLTs was comparable to untreated PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
196
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(199 citation statements)
references
References 29 publications
(42 reference statements)
1
196
2
Order By: Relevance
“…In contrast to the low incidence of ALI (5/645, 0.8%) reported by the clinical investigators during conduct of the clinical trial, 13 the EPP review using AECC criteria observed a higher frequency of ALI (35/645, 5.4%). We believe this difference was due to the use of specific criteria for the diagnosis of ALI, including ARDS, by the expert panel and the lack of a specific code for ALI in the MedDRA coding dictionary used in the initial clinical trial.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…In contrast to the low incidence of ALI (5/645, 0.8%) reported by the clinical investigators during conduct of the clinical trial, 13 the EPP review using AECC criteria observed a higher frequency of ALI (35/645, 5.4%). We believe this difference was due to the use of specific criteria for the diagnosis of ALI, including ARDS, by the expert panel and the lack of a specific code for ALI in the MedDRA coding dictionary used in the initial clinical trial.…”
Section: Discussioncontrasting
confidence: 58%
“…AEs were coded using the Medical Dictionary for Regulatory Activities (MedDRA) terminology (version 3.3) to Preferred Term (PT) and mapped to the primary and nonprimary respiratory, thoracic, and mediastinal disorders System Organ Class (SOC), and the frequencies of the respective AEs were calculated (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). 13 No PT for ALI was available in version 3.3 of MedDRA. During the conduct of the SPRINT trial, investigators were not provided with specific per-protocol criteria for the diagnosis of ALI or ARDS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations